Proceedings of the 1999 IEEE International Symposium on Electronics and the Environment (Cat. No.99CH36357) 1999
DOI: 10.1109/isee.1999.765864
|View full text |Cite
|
Sign up to set email alerts
|

Environmental performance of mobile products

Abstract: 129.9 58.9 ----202 102

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…A power delivery of 2 W per node is an adequate requirement for battery-driven wearable systems where the nodes are designed to have low power consumption in order to enable a long battery lifetime. This requirement is adopted from the mobile electronics industry where 2 W is a maximum power rate for such products [10]. The bandwidth requirement has to be set in order to accomplish a data transfer rate up to 1 Mbit/s assuming baseband signal with zero DC component as communication signal, e.g., Manchester format, non-return-to-zero bipolar format, etc.…”
Section: Dc-plc Transceiver Requirementsmentioning
confidence: 99%
“…A power delivery of 2 W per node is an adequate requirement for battery-driven wearable systems where the nodes are designed to have low power consumption in order to enable a long battery lifetime. This requirement is adopted from the mobile electronics industry where 2 W is a maximum power rate for such products [10]. The bandwidth requirement has to be set in order to accomplish a data transfer rate up to 1 Mbit/s assuming baseband signal with zero DC component as communication signal, e.g., Manchester format, non-return-to-zero bipolar format, etc.…”
Section: Dc-plc Transceiver Requirementsmentioning
confidence: 99%
“…Those studies demonstrated that the production and disposal of certain mobile phone components, such as PCBs, electronic components, and batteries, have important impacts on the environment, including in terms of acidification and nitrification, climate change, and resources (Yang et al, 2004;Singhal and Nokia Corporation, 2005). It has also been shown that the extraction of raw materials used to produce mobile phones, the use of mobile phones, and the disposal of WMPs have strong impacts on the environment (Ram et al, 1999;Yu et al, 2010;Herrmann and PE International, 2008;Park et al, 2006). However, little research on the environmental impacts of WMP recycling processes has been performed using the LCA method, although some studies of remanufacturing processes, WMP retrievability, and the ecological efficiencies of recycling and retrieving rare metals have been carried out (DeVierno, 2011;Socolof et al, 2006;Huisman, 2003;Skerlos et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although digitization can increase accessibility to and portability of digital music, it has been suggested that greater portability could itself encourage a greater uptake of digital music and, of course, of the portable devices themselves (Alakeson and Türk 2003). Despite efficiency improvements in electronic hardware, concern has been expressed about increased uptake reversing these gains (Ram et al 1999; Plepys 2001).…”
Section: Introductionmentioning
confidence: 99%